Functional Status of Hypothalamic–Pituitary–Thyroid and Hypothalamic–Pituitary–Adrenal Axes in Hospitalized Schizophrenics in Shanghai - Zhu, Yuncheng; Ji, Haifeng; Tao, Lily; Cai, Qing; Wang, Fang; Ji, Weidong; Li, Guohai; Fang, Yiru (Frontiers in Psychiatry, 2020)
Objective Neuroendocrine dysfunction is related to the pathogenesis of mental disorders, but conclusions from clinical research lack consistency. We aimed to investigate the neuroendocrinal pathophysiology and its correlation with clinical symptoms in patients with schizophrenia. Methods The present cross-sectional study included 486 inpatients with schizophrenia admitted at a psychiatric hospital in Shanghai within one year, and 154 healthy controls (HC) matched on age and gender. The serum hemoconcentrations of thyroid-stimulating hormone (TSH), total triiodothyronine (TT3), total thyroxine (TT4), free triiodothyronine (FT3), free thyroxine (FT4), adrenocorticotrophic hormone (ACTH), and cortisol (COR) were measured via electrochemical luminescence immunoassay. Pathophysiological conversions of neuroendocrine were then associated with gender, age, age at onset, antipsychotic treatment using hierarchical multiple linear regression. Results When compared to HC, the schizophrenia group showed elevated ACTH and COR levels and decreased TT3 and TT4 levels (p‘s < 0.05). First-episode patients showed lower TSH and higher FT3 and FT4 (p’s < 0.05) compared to recurrent patients. Female patients showed higher TSH and lower TT3, FT3, and ACTH levels (p’s < 0.05) compared to males. We observed the area under the curve (AUC) of the predictive model to distinguish between schizophrenia and HC to be 0.737 among total samples and between first-episode and recurrent schizophrenia to be 0.890 among subgroups. Conclusions Decreased TT3 and TT4 and elevated ACTH and COR levels appear to be associated with schizophrenia symptoms. The chronic recurrent trait of schizophrenia may cause long-term effects on FT3 and FT4 while changes in thyroid, and adrenal function as a result of mental disorder varied with gender. The pathophysiological parameters provide fair to good accuracy of these models.